A Novel Method for Fabricating Double Layers Porous Anodic Alumina in Phosphoric/Oxalic Acid Solution and Oxalic Acid Solution. (8th May 2016) - Xu, Yanfang; Li, Xiaojiu; Liu, Hao; Xu, Jie
Abstract : A novel method for fabricating ordered double layers porous anodic alumina (DL-PAA) with controllable nanopore size was presented. Highly ordered large pore layer with interpore distance of 480 nm was fabricated in phosphoric acid solution with oxalic acid addition at the potential of 195 V and the small pore layer was fabricated in oxalic acid solution at the potential from 60 to 100 V. Experimental results show that the thickness of large pore layer is linearly correlative with anodizing time, and pore diameter is linearly correlative with pore widening time. When the anodizing potential in oxalic acid solution was adjusted from 60 to 100 V, the small pore layers with continuously tunable interpore distance from 142 to 241 nm and pore density from1.94 × 10 9 to4.89 × 10 9 cm −2 were obtained. And the interpore distance and the pore density of small pore layers are closely correlative with the anodizing potential. The fabricated DL-PAA templates can be widely utilized for fabrication of ordered nanomaterials, such as superhydrophobic or gecko-inspired adhesive materials and metal or semiconductor nanowires.